Evaluation of Brinjal (Solanum melongena L.) Genotypes for yield and Resistance to Shoot and Fruit Borer (Leucinodes orbonalis Guen.) - Daliya T (Department of plant Breeding and Genetics, College of Agriculture, 2001)
The present investigation on evaluation of yield and resistance to shoot and fruit borer of brinjal genotypes was conducted at the Department of Plant Breeding and Genetics, College of Agriculture, Vellayani, during the period 2000 - 2001. Data for the study was collected from two field experiments. For the evaluation of yield and its component characters of the 25 brinjal genotypes, a field experiment was conducted in randomised block design with three replications. Analysis of variance revealed significant difference among the genotypes for all the characters studied. Grouping of genotypes revealed that the genotypes VI (Swetha), V2 (Surya) and V18 (Pusa Purple Cluster) were better as far as yield per plant, number of fruits per plant and number of harvests were concerned. Pus a Kranti (V 17) had better fruit length, girth and weight. High phenotypic coefficient of variation and genotypic coefficient of variation were observed for yield per plant, number of fruits per plant, number of harvests, number of leaves per plant and number of secondary branches per plant. High heritability coupled with high genetic advance was also observed for these characters. At genotypic level, yield per plant showed high positive correlation with number of harvests, number of fruits per plant and fruit weight. The path analysis showed that number of harvests, fruit weight and number of